RANCANG BANGUN ALAT PRES KONVENSIONAL UNTUK PARUTAN UBI KAYU SKALA INDUSTRI RUMAH TANGGA - Amin Saputra; Indah Widanarti; Yosefina Mangera (Musamus AE Featuring Journal, 2020)
Pressing is one solution to reduce the water content in grated cassava to reduce the risk of decreasing the quality of cassava due to enzymatic activity by microbes or fungi. The pressing of grated cassava by the community in Wenda Asri Village, Jagebob District, Merauke Regency is to put the grated cassava into a sack, squeeze it using a board and rotate it slowly until the water comes out. This method takes a long time, so a more efficient press is needed. Based on the literature study, the main components of the press tool are the frame, stainless steel plate and aluminium as the tool stands, and iron axle and press plate as a pressing device. The dimensions of the grated cassava press are 40 cm long, 40 cm wide and 120 cm high, with a maximum capacity of 15 kg of a conventional grated cassava press. The process of operating the traditional press tool for grated cassava was carried out three times, with the amount of tested grated cassava, namely: 2.5 kg; 5 kgs; and 15 kg. Based on the initial test results, the water content of grated cassava with the maximum capacity before pressing was 61.7% wb, and the water content after pressing was 48.2% wb. The second test results showed that the water content of grated cassava with a capacity of 2.5 kg and 5 kg before pressing was 60.7% wb and after being pressed with a capacity of 5 kg was 44.5% wb.